PENGARUH BEASISWA KIP-K TERHADAP MOTIVASI BELAJAR MAHASISWA PENDIDIKAN EKONOMI UNIVERSITAS PANCA SAKTI BEKASI - NIA LESTARI; EKA PUTRI; JONI TESMANTO (GANEC SWARA, 2024)
This research discusses the influence of the KIP-K scholarship on learning motivation at Panca Sakti University Bekasi. Using a quantitative method and simple linear analysis, a questionnaire was distributed to 59 students of Economic Education at Panca Sakti University Bekasi. The KIP-K scholarship has a direct impact on learning motivation. This is evidenced by a value of 76.1%, indicating that the KIP-K scholarship influences learning motivation by 76.1%, while other components not examined in this study account for the remaining portion. Therefore, the KIP-K scholarship is an important factor that must be considered to foster learning motivation.